ANALYSIS OF ROUTER ATTACK WITH SECURITY INFORMATION AND EVENT MANAGEMENT AND IMPLICATIONS IN INFORMATION SECURITY INDEX - CITRA ARFANUDIN; Bambang Sugiantoro; Yudi Prayudi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2019)
Information security is a need to secure organizational information assets. The government as the regulator issues an Information Security Management System (ISMS) and Information Security Index (US) as a measure of information security in the agency of a region. Security Information and Event Management (SIEM) is a security technology to secure information assets. SIEM is expected to provide information on attacks that occur on the router network and increase the value of the Indeks KAMI of government agencies. However, the use of SIEM is still questionable whether it can recognize a router attack and its impact on the value of our index. This research simulates attacks on routers with 8 attacks namely Mac Flooding, ARP-Poisoning, CDP Flooding, DHCP Starvation, DHCP Rogue, SYN Flooding SSH Bruteforce and FTP Bruteforce. 8 types of attacks followed by digital forensic analysis using the OSCAR method to see the impact on routers and SIEM. Also measured is index KAMI before and after the SIEM to be able to measure the effect of SIEM installation on the value of index KAMI. It was found that the use of SIEM to conduct security monitoring proved successful in identifying attacks, but not all were recognized by SIEM. SIEM only recognizes DHCP Starvation, DHCP Rogue, SSH Bruteforce and FTP Bruteforce. Mac Flooding, ARP-Poisoning, CDP Flooding, SYN Flooding attacks are not recognized by SIEM because routers do not produce logs. Also obtained is the use of SIEM proven to increase our index from the aspect of technology